Glutaminyl Cyclases as Novel Targets for the Treatment of Septic Arthritis - Hellvard, Annelie (Oxford University Press, 2013)
Background. Septic arthritis is a severe and rapidly debilitating disease mainly caused by Staphylococcus aureus. Here, we assess the antiarthritic efficiency of glutaminyl cyclase (QC) inhibitors. Methods. Mice were inoculated with an arthritogenic amount of S. aureus intravenously or by local administration into the knee joint. Animals were treated with QC inhibitors (PBD155 and PQ529) via chow during the experiment. QC and isoQC knockout mice were also analyzed for arthritis symptoms after local administration of bacteria. Results. Both QC inhibitors significantly delayed the onset of clinical signs of arthritis, and inhibitors significantly decreased weight loss in treated animals. Following intraarticular injection of S. aureus, PBD155-treated mice had lower levels of synovitis and bone erosion, as well as less myeloperoxidase in synovial tissue. Fluorescence-activated cell sorter analysis revealed that PBD155 treatment affected the expression pattern of adhesion molecules, preventing the upregulation of cells expressing CD11b/CD18. Conclusion. The compounds investigated here represent a novel class of small molecular antiarthritic inhibitors. In our studies, they exerted strong antiinflammatory actions, and therefore they might be suited for disease-modifying treatment of infectious arthritis.